Digital mental health interventions for substance use prevention among youths in the Niger Delta: a systematic review - Adika, David T.; Ukoba, Obatavwe (International Journal Of Community Medicine And Public Health, 2025)
Digital mental health interventions (DMHIs) offer a promising, accessible, and less stigmatizing approach to combating the global challenge of youth substance use, a critical issue amplified in the Niger Delta due to socio-economic factors and limited healthcare access. This review synthesized findings on DMHI effectiveness, technologies, strengths, and limitations, with implications for the Niger Delta. While DMHIs effectively address general youth mental health, direct evidence for primary substance use prevention is limited, often focusing on early intervention with an alcohol-centric bias. Web-based and mobile apps are preferred technologies, showing high youth acceptability. Key strengths include accessibility, reach, and engagement; however, challenges like low adherence, limited long-term data, and methodological quality persist. Crucially, interventions need cultural adaptation and sustainable funding, especially in regions like Sub-Saharan Africa where a significant gap in youth mental health DMHIs exists and digital access varies. Successful implementation in the Niger Delta requires context-specific, culturally appropriate DMHIs that address diverse substances, incorporate human support, and ensure rigorous evaluation.